2013
DOI: 10.6000/1929-6037.2013.02.04.2
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Potentiometric Study of Al3+ and Cr3+ with Malic Acid in Aqueous Solutions

Abstract: It appeared that malic acid solubilized both Al 3+ and Cr 3+ in aqueous solutions at all pH-values in 0.1 M NaNO3 at 25 o C. The detailed potentiometric measurements indicated that these free tri-valent metal ions released a net of three protons (3H + 's) into the solution. Free malic acid released a net of (2H + 's) into the solution from the two carboxylates. However, in the presence of metal ions malic acid effectively releases a net of three protons (3H + 's) into the solution; two from the two carboxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The only general data on the complexation constant of Cr(III) with malic acid, which is 5.4, was reported by Mo et al (2018) . On the basis of our experimental data and the incidence of Cr-malate complexes proposed by Hamada et al (2013) , we can conclude that the first Cr-malate peak (0.7–1.4 min), which is weakly bound to the column resin, most likely corresponds to [Cr(mal)(OH)] − , the broadened Cr-malate peak (2.0–3.2 min) to the mixture of the Cr-malate oligomeric complexes, while that eluted from 5.0 to 5.6 min, to the [Cr 2 (mal) 2 (OH) 3 ] 3− complex. To prove that the first eluted Cr peak is the Cr-malate complex, and not ionic Cr, the speciation of Cr was also performed with a solution of ionic Cr(III) and Cr-malate at the pH 3.5 and 6.5.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The only general data on the complexation constant of Cr(III) with malic acid, which is 5.4, was reported by Mo et al (2018) . On the basis of our experimental data and the incidence of Cr-malate complexes proposed by Hamada et al (2013) , we can conclude that the first Cr-malate peak (0.7–1.4 min), which is weakly bound to the column resin, most likely corresponds to [Cr(mal)(OH)] − , the broadened Cr-malate peak (2.0–3.2 min) to the mixture of the Cr-malate oligomeric complexes, while that eluted from 5.0 to 5.6 min, to the [Cr 2 (mal) 2 (OH) 3 ] 3− complex. To prove that the first eluted Cr peak is the Cr-malate complex, and not ionic Cr, the speciation of Cr was also performed with a solution of ionic Cr(III) and Cr-malate at the pH 3.5 and 6.5.…”
Section: Resultsmentioning
confidence: 63%
“…Cr-malate ( Figure 1B ) is eluted as a dominant peak with the solvent front from 0.7 to 1.4 min, as a small, broadened peak from 2.0 to 3.2 min and as a larger peak from 5.0 to 5.6 min. Based on data from the potentiometric titrations, Hamada et al (2013) proposed the formation of mixed hydroxo-malate [Cr(mal)(OH)] − and the dimeric [Cr 2 (mal) 2 (OH) 3 ] 3− complexes as major Cr-malate species. The authors also did not exclude the possibility of oligomeric complexes being formed.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility was that increasing the maleicA concentration may lead to the formation of a more active complex. A previous study reported that the Al(III)−malicA complex evolved from monomeric to dimeric species as the malicA loading increased, 46 suggesting the need for optimization of the complex geometries in future investigations. This study underscores that the use of maleicA (or malicA) at an optimal dosage can serve as an environmentally friendly approach to increase the system selectivity without compromising the catalytic rate.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%